Climate-Smart Agriculture Solutions for Egypt: What IFAD can do… and can’t do! - Tremblay, Nicolas (2019)
As part of the IFPRI Egypt Seminar in partnership with the American University in Cairo: “Climate-Smart Agriculture Solutions for Egypt”